PENENTUAN VOLUME SAMPAH DI LEMBAGA BINTANG SEJAHTERA - Mukhtar, Mukhtar; Alawiyah, Tuty; Jannah, Wardatul (Jurnal Ilmiah IKIP Mataram, 2018)
In this study, the volume of waste has been determined in Bintang Sejahtera Institution. In this study several stages were carried out, namely transportation, first weighing, first weighing, sorting, and calculation. In the sorting phase, some data is needed to select the volume of waste, namely the date of arrival of goods, types of goods, suppliers, goods tonnage, supplier tonnage, buyer tonnage. The results showed that there were 34 types of waste obtained by Bintang Sejahtera Institution with the total amount of waste each month reaching an average of 7756 tons / month from 34 types of waste received at Bintang Sejahtera Institution